Hubungan Antara Perilaku Olahraga Dan Merokok Dengan Kejadian Hipertensi Di Wilayah Kerja Puskesmas Kartasura Kabupaten Sukoharjo - Wahyuningsih, Dwi; , Bejo Raharjo, SKM, M.Kes; , Farid Setyo Nugroho, SKM (2015)
Hypertension is a health problem in the world by continues sustained. Hypertension can cause complications such as stroke, heart attack, heart failure, and kidney failure. Hypertension or high blood pressure is a condition where blood vessels to increase blood pressure. Adult's normals blood pressure is 120/80 mmHg. Someone was said that he has hypertension if his systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. Objective husband was to analyze the relation between review sport and smoking behavior with incidence of hypertension in local government clinic work area of Kartasura district Sukoharjo regency. Research husband with quantitative analytical cross-sectional study design. Husband research done in local government clinic work area of Kartasura district Sukoharjo regency with sample 137 people. Sampling using simple techniques purposive sampling while testing techniques using Chi Square statistics. Research shows that the initials no relation between Sports Behavior with incidence of hypertension (p=0048>α=0.05; RP=1.425; 95%CI:0,987-2,058). There is a relation between smoking and the incidence of hypertension (p=0048<α=0,05; RP=1,477; 95%CI:1.016-2.148) in local government clinic work area of Kartasura district Sukoharjo regency. Keywords: Behavior, Hypertension, Smoking, Sports